Transforming agrifood systems to achieve China’s 2060 carbon neutrality goal - Zhang, Yumei; Fan, Shenggen; Chen, Kevin Z.; Feng, Xiaolong; Zhang, Xiangyang; Bai, Zhaohai; Wang, Xiaoxi (2021)
During recent decades, agriculture has developed rapidly in China, ensuring food security and enriching residents’ diets. At the same time, greenhouse gas (GHG) emissions from the country’s agrifood systems have increased by only 16 percent in the past two decades and fell for two consecutive years in 2017 and 2018. The proportion of GHG emissions in the country’s food systems to the total GHG emissions dropped from 18.7 percent in 1997 to 8.2 percent in 2018. GHG emissions from the Chinese agrifood systems should not be ignored, neverthless. In 2018, GHG emissions from agrifood systems was still as high as 1.09 billion tons CO2eq1. While ensuring food security as the national top priority, measures such as improving agricultural technologies, reducing food loss and waste, and shifting dietary patterns must be adopted to reduce GHG emissions from agrifood systems. Improvements in agricultural technologies are the most effective standalone measures, but the combined three measures above have the most significant effect on GHG emission reduction. Projections show that the combined three measures can redcue GHG emissions by 47 percent in 2060 from the 2020 level. Land use, land use change, and forestry (LULUCF) play a key role as a carbon sink. The carbon sequestration from LULUCF was around 1.1 billion tons CO2eq in 2014. It can increase to 1.6 billion tons of CO2eq per year in 2060, thus LULUCF could completely offset GHG emissions from agrifood systems and still have a surplus capacity to sequester nearly 1 billion additional tons of CO2eq per year, well above the current level of net sequestration,contributing to overall carbon neutrality of China.